Bons tempos aqueles: implicações na expansão do campo dêitico - Santos, Caio César Costa (2014)
This dissertation reveals the implications of indices subjectivity of deictic expressions and translocation of these same linguistic forms in terms of memory. The central hypothesis is that deictic field is expanded through coemergency crystallized indexical thoughts (in memory) via referential expressions, such as grip, almost unanimously, by demonstrative noun phrases. From this hypothesis, it is necessary the extension of the concept of deictic field as recent deictic conception has not yet outlined this objective. Benveniste had already presupposed processes for this problem: a spatio-temporal translocation and of plans difference in enunciative studies. We based this description in order to frame the problem investigated here: (a) if the deictic field of memory is possibly the "I - here - now", how to define and characterize this typicality of referent;? (b) how to explain this phenomenon of expansion of the deictic field of perceptual coordinates in memories-images inside their own "I- here - now" via demonstratives determinants of employment ; (c) how the tags and expansions of deictic memory (structured demonstrative pronouns) are revealed in the textual dynamics and how referential and discursive functions? The concluding observations point to the fact that the preferred choice by the indices demonstration is in accordance with different conditionings of deictic operations, including memory that do not share the same experiences of situational mostrative field. In contrast, memory anchored in a reference treatment limited in contextual motivation that appropriates the deictic field.